2006
DOI: 10.1111/j.1523-1739.2006.00540.x
|View full text |Cite
|
Sign up to set email alerts
|

Decline in Relative Abundance of Bottlenose Dolphins Exposed to Long‐Term Disturbance

Abstract: Studies evaluating effects of human activity on wildlife typically emphasize short-term behavioral responses from which it is difficult to infer biological significance or formulate plans to mitigate harmful impacts. Based on decades of detailed behavioral records, we evaluated long-term impacts of vessel activity on bottlenose dolphins (Tursiops sp.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
441
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 530 publications
(448 citation statements)
references
References 36 publications
4
441
1
2
Order By: Relevance
“…Recent studies have demonstrated that human‐generated sound can detrimentally affect animal hearing, communication, movements, and foraging (Shannon et al., 2015; Slabbekoorn et al., 2010). However, it is difficult to translate these effects into meaningful predictions about individual fitness and population‐level consequences, (Morley, Jones, & Radford, 2014) because animals could possibly move away from sound sources, the disturbance may be transient and the animals could compensate to prevent long‐term impacts (Bejder et al., 2006). Therefore, it is imperative there are more experimental studies performed on organisms that can be tracked to investigate directly whether common sources of human‐generated sound disrupt behavior and/or reduce survival (Simpson et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that human‐generated sound can detrimentally affect animal hearing, communication, movements, and foraging (Shannon et al., 2015; Slabbekoorn et al., 2010). However, it is difficult to translate these effects into meaningful predictions about individual fitness and population‐level consequences, (Morley, Jones, & Radford, 2014) because animals could possibly move away from sound sources, the disturbance may be transient and the animals could compensate to prevent long‐term impacts (Bejder et al., 2006). Therefore, it is imperative there are more experimental studies performed on organisms that can be tracked to investigate directly whether common sources of human‐generated sound disrupt behavior and/or reduce survival (Simpson et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Cetacean-based tourism is one of these growing potential threats and has resulted in increased exposure of dolphin and whale populations to high levels of boat traffic and disturbance (e.g. Bejder et al 2006b;Stensland and Berggren 2007;Stamation et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, management strategies can be modified depending on the habitat scale of the targeted animals, for example, resident versus non-resident populations, and/or the intensity of interactions with vessels (see e.g. Bejder et al 2006b;Stockin et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Short-term impacts associated with boat interactions include group directional changes (Steckenreuter, Möller, & Harcourt, 2012;, changes in group dispersion (Arcangeli & Crosti, 2009;Steckenreuter et al, 2012), heightened breathing synchrony (Hastie, Wilson, Tufft, & Thompson, 2003), increased dive times (Lusseau, 2003b) and changes in vocalizations (Buckstaff, 2004;Scarpaci, Bigger, Corkeron, & Nugegoda, 2000). Such changes can have longer lasting impacts resulting in seasonal (Rako et al, 2013) or long-term (Bejder et al, 2006) displacement and increased energy expenditure (Williams, Lusseau, & Hammond, 2006).…”
mentioning
confidence: 99%